Identification of a genetic locus of Haemophilus influenzae type b necessary for the binding and utilization of heme bound to human hemopexin. - Hanson, M S (1992)
The mechanism(s) used by Haemophilus influenzae to acquire the essential nutrient heme from its human host has not been elucidated. The heme carried by the high-affinity serum protein hemopexin is one potential source of this micronutrient in vivo. A colony-blot assay revealed that heme-human hemopexin-binding activity was shared among most capsular serotype b strains of H. influenzae but was uncommon among other strains. We have identified a recombinant clone binding heme-human hemopexin from a H. influenzae type b (Hib) genomic library expressed in Escherichia coli. Both the Hib strain and the heme-hemopexin-binding clone expressed a polypeptide of approximately 100 kDa that bound radiolabeled heme-hemopexin. Oligonucleotide linker insertion mutagenesis of the plasmid DNA from this recombinant clone was used to confirm that expression of the 100-kDa protein correlated with the heme-hemopexin-binding activity. Exchange of one of these mutant alleles into the Hib chromosome eliminated expression of both the 100-kDa protein and the heme-hemopexin-binding activity. Furthermore, this Hib mutant was unable to utilize heme-human hemopexin as a heme source.